Institute develops seed bank - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Niger-based branch of the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), has recently set up a gene bank for some 5,540 varieties of groundnuts and 1,500 varieties of millet. The bank will help to stem the...